Розробка інформаційної системи книжкової крамниці з рекомендаційною функцією, що реалізується методами Data Mining - Другак, А. О. (ХНУРЕ, 2023)
The report considers the stages of designing and creating an e-commerce information system with a recommendation function for customers. To implement the recommendation functions of the information system, methods are used, which implement the classification of customers according to certain characteristics and the search for associative rules based on the history of book purchases.